Clinical and functional results of modified femtolaser refractive autokeratoplasty in patients with keratoconus - A.V. Tereshchenko; M.A. Timofeev; I.G. Trifanenkova; S.K. Demyanchenko (Офтальмохирургия)
Purpose. To analyze the clinical and functional results of modified femtolaser refractive autokeratoplasty and evaluate its effectiveness in patients with keratoconus during a follow-up period of 36 months. Material and methods. The study included 24 patients (13 men and 11 women) diagnosed with stage 2 keratoconus according to the Amsler, 1998 classification. The age of the patients ranged from 25 to 37 years (mean 31±6 years). Taking into account the initial parameters of the spherical and cylindrical components, as well as biometric parameters, which indicated the deliberate ineffectiveness of intrastromal keratoplasty (ISKP) in this group, all patients were performed femtolaser refractive autokeratoplasty (FRAK) according to a modified technique using a Femto LDV Z8 femtolaser unit (Ziemer, Switzerland). Results. An analysis of the clinical and functional results of the modified FRAK technique for topographically centrally located keratoconus showed that this technology provides a stable refractive effect in patients with stage 2 keratoconus during a follow-up period of 36 months. Performing personalized FRAK according to indications provides an increase in corrected visual acuity already in the early postoperative period with a tendency to further increase an average up to 0,46±0,08 by 36 months after surgery, as well as stable state of the ecstatic process throughout the entire follow-up. Conclusion. The modified FRAK technology is effective and can be successfully used in the early stages of keratoconus in cases with initial low visual acuity and axial myopia.